Allicin enhances urea-N conversion to microbial-N by inhibiting urease activity and modulating the rumen microbiome in cattle - Shiqi Zhang; Nan Zheng; Shengguo Zhao; Jiaqi Wang (Microbiome)
Abstract Background Urea serves as a vital nonprotein nitrogen source in ruminant nutrition, but its efficient utilization is often hampered due to rapid urease activity in the rumen. This study explores the potential of allicin, a garlic-derived compound, as a urease inhibitor to improve urea nitrogen utilization. Enzyme inhibition kinetics and molecular docking were used to identify allicin’s interaction sites on urease. Additionally, metagenomic and 15N-urea metabolic flux analyses were conducted to evaluate allicin’s impact on microbial populations and urea-N metabolism. Results Allicin was identified as an inhibitor of ruminal urease, with an IC 50 of 126.77 ± 1.21 μM. Molecular docking studies have shown that allicin forms hydrogen bonds with key urease residues, leading to the preemption of the urease active site and thus impeding urea binding. In a simulated rumen environment, allicin significantly reduced urea hydrolysis and ammonia production. Furthermore, allicin modified the rumen microbial community by inhibiting Prevotella species while promoting the growth of Ruminobacter species and Denitrobacterium detoxificans. A 15N-urea metabolic flux analysis revealed that allicin facilitated the incorporation of urea-derived nitrogen into microbial amino acids and nucleotides. Conclusion Allicin effectively inhibits urease activity in the rumen, enhancing the conversion of urea-N into microbial biomass. These findings suggest that allicin has significant potential to optimize urea metabolism in the rumen, offering a novel strategy for improving ruminant nitrogen nutrition. Video Abstract